FAKTOR RESIKO GANGGUAN STRESS PASCA TRAUMA PADA ANAK KORBAN PELECEHAN SEKSUAL - Hera Wahyuni (Khazanah Pendidikan, 2016)
The aim of this study to research deeply on Risk Factors For Post Traumatic Stress Disorder (PTSD) in children Sexual Abuse. The method used to conduct this study from including a variety of sources: 1) results abstract of scientific writing, 2) review journals. Selection of the article focuses on children sexual abuse who experience PTSD, review articles carried in the last 11 years ranging from 2005 to 2015, consists of 35 articles that analyzed the risk factors for PTSD in cases traumatic as sexual abuse. PTSD is an ongoing maladaptive reaction to a traumatic event that involves death or threat of death or serious physical harm or threats to the safety of themselves or others. Individuals who experience PTSD can be seen from three of the following symptoms: 1) re-experiencing of events traumatic , 2) avoidance, 3) hyperarousal, have difference in symptoms between children and adults, symptoms in children is usually characterized by bedwetting, speech disorders, poor attachment, etc. As for the risk factors associated with PTSD in children sexual abuse have two (2) factors : 1) vulnerability factors in children and 2) environmental factors (family and social). These two factors, will be broken down into three phases trigger PTSD in children are : 1) Pre-Trauma, 2). Peri-Trauma, and 3). Post-Trauma. Kata Kunci : Post Traumatic Stress Disorder (PTSD), Children, Sexual Abused.